Phytochemicals Rosmarinic Acid, Ampelopsin, and Amorfrutin-A Can Modulate Age-Related Phenotype of Serially Passaged Human Skin Fibroblasts in vitro - Sodagam, Lakshman; Lewinska, Anna; Kwasniewicz, Ewa; Kokhanovska, Sofiya; Wnuk, Maciej; Siems, Karsten; Rattan, Suresh I. S. (Frontiers in Genetics, 2019)
One of the aims of the EU-funded Research and Innovation Action (RIA), titled “Ageing with Elegans” is to enhance better understanding of the factors causing health and disease in aging, and develop evidence-based preventive, diagnostic, therapeutic and other strategies. The work package-5 of this project is focused on testing the effects of phytochemicals of natural and synthetic origin on aging, longevity and health of human cells in vitro, after the initial screening using the animal model systems of nematodes and rats and mice. Accordingly, the first series of three compounds, rosmarinic acid (ROSM), ampelopsin (AMPEL) and amorfrutin-A (AMOR), were selected to test for their short-term and long-term effects on human skin fibroblasts undergoing aging and senescence in vitro. The lifelong modulatory effects of these compounds were tested individually at two doses (0.5 and 1.0 µM), selected after a short-term dose response check of a 20-thousand-fold range (0.01 to 200 µM). The results show that these compounds do have some beneficial effects in terms of supporting the long-term lifelong growth and enhanced stress tolerance of serially passaged cells. These effects seem to be achieved by reducing the extent of loss of telomeres, of 5-methyl-cytosine (5-mC) and of 5-hydroxymethyl-cytosine (5-hmC), by reducing the accumulation of oxidative DNA damage product 8-OHdG. There is also some indication that these compounds induce at least one of the stress responses in terms of the increased synthesis of heat shock protein Hsp70. Thus, these phytochemicals may be potential hormetins, which bring about their health beneficial effects by the phenomenon of mild stress-induced hormesis.